Investment Control in Denpasar City - Anggraeni, Komang Ayu Trina (Journal of A Sustainable Global South, 2024)
Enhancing the business climate and boosting investment are conducted within the city's jurisdiction. Denpasar City has endeavored to draft the General Investment Plan (RUPM), but progress has stalled because Bali Province has not completed its RUPM. To address this issue, Denpasar City has initiated Investment Potential Mapping. This mapping aims to provide valuable insights to potential investors interested in investing in Denpasar. This policy paper is prepared using data collection and data processing methods. Data collection involves interviews, document studies, and Focus Group Discussions (FGD). Data processing employs descriptive and comparative methods.